Characterization of Anti-bacterial Compounds from the Seed Coat of Chinese Windmill Palm Tree (Trachycarpus fortunei) - Ahmed, Shakeel; Liu, Huimin; Ahmad, Aqeel; Akram, Waheed; Abdelrahman, Eman K. N.; Ran, Fengming; Ou, Wuling; Dong, Shuang; Cai, Qian; Zhang, Qiyun; Li, Xiaohua; Hu, Sheng; et al. (Frontiers in Microbiology, 2017)
The increasing of multidrug resistance in bacterial associated infections has impaired the current antimicrobial therapy and it forces the search for other alternatives. In this study, we aimed to find the in vitro antibacterial activity of seed coat of Trachycarpus fortunei against a panel of clinically important bacterial species. Ethanolic extracts of target tissues were fractionated through macro porous resin by column chromatography, using ethanol as an organic solvent with a concentration gradient of 0–100%, each along with 20% concentration increment. The minimum inhibitory (MIC) concentrations of all fractions were measured. It is found that 20% ethanolic fraction showed the most significant inhibition against tested bacterial species. All fractions were analyzed by Ultra-Performance Liquid Chromatography/mass spectrometry (UPLC/MS) and compounds were identified by comparing mass spectra with standard libraries. By pairing the identified compounds from different fractions with the antibacterial activity of each fraction, it was shown that compounds stearamide (7), 1-(4-Fluorophenyl)-2-(methylthio)-1H-imidazole-5-carboxylic acid (9) and 2,4,5 triacetoxybiphenyl (10) topped in the list for anti-bacterial activity. Further experiment with pure chemicals verified that compounds 9 and 10 have antibacterial activity against Gram-negative bacteria. Whereas, the lowest MIC value (39.06 μg/mL) was obtained by compound 10 against Staphylococcus epidermidis. Hence, the seed coat of T. fortunei with its antimicrobial spectrum could be a good candidate for further bactericidal research.